Pharyngeal Airway Dimensions and Head Posture in Obstructive Sleep Apnea Patients with and without Morphological Deviations in the Upper Cervical Spine - Liselotte Sonnesen; Arne Petersson; Søren Berg; Palle Svanholt (eJournal of Oral Maxillofacial Research, 2017)
Objectives: The aim of the study was to analyse differences in pharyngeal airway dimensions and head posture between obstructive sleep apnea patients with and without morphological deviations in the upper cervical spine and to analyse associations between pharyngeal airway dimensions and head posture in the total sample.